G245(P) Pitfalls in Weight Estimation. (4th June 2013) - Harlow, G; Jayatunga, R
Abstract : Children and infants of different age and weight respond differently to drugs. Special care is needed in the calculation of drug doses to reduce and prevent the risk of toxicity. The 2011 Advanced Paediatric Life Support (APLS) guideline, 5th edition, includes an updated method for weight estimation for emergency situations[1]. Aims: We aim to study our population of patients to determine whether their actual weights are congruent with the updated APLS weight estimation. We also compare with the 2005 APLS weight estimate calculation[2]. Method: Prospective audit at a large two-site NHS trust with a 23-hour paediatric assessment unit and two in-patient wards. The catchment population for our study has a higher proportion of population in lower socioeconomic groups than the national average[3]. The age, basic diagnosis and weight of consecutive presenting children between 1 month and 12 years were collected for 166 patients in December 2012. We aim to collect data to March 2013 with an estimated sample size of 500. Children were weighed on Seca baby/standing/chair scales (Seca, Hamburg, Germany) with children under two naked and over two wearing minimum clothing without shoes. Percentage weight difference between child's actual weight and their expected weight was calculated using both the 2005 APLS formula, weight(kg) = (age +4) × 2 and the 2011 formulae: 1–12 months: weight(kg) = (0.5 × age in months)+4; 1–5 years: weight(kg) = (2 × age in years) +8; 6–12 years: weight(kg) = (3 × age in years) +7 Results: Table 1: Mean weight differences by age Preliminary results outlined in Table 1 demonstrate that although the 2011 APLS calculation is better for weight estimation in our 6–12 years age group than the 2005 calculation, there is still the potential for significant underestimation of weight in all ages. Conclusion: Weight estimation is extremely important for paediatric resuscitation and emergency treatment. However, across all age groups weight estimation is no substitute for establishing the child's actual weight at the earliest opportunity. References: Advanced Life Support Group. APLS, Fifth Edition. Blackwell 2011. Advanced Life Support Group. APLS, Fourth Edition. Blackwell 2005. 2011 Census: Key Statistics for local authorities in England and Wales. Office for National Statistics; December 2012.